A PRESENTATION OF A CASE OF A CHILD SUFFERING FROM AUTISM - Vesna Lazarovska; Zhivka Dimitrovska (Filozofski fakultet Skopje, 2005)
The most intense period in the discourse and language is within the first three years form one’s life, a period when the brain develops and grows. These abilities can be best developed in an environment full of sounds, emotions, looks and consistent exposure to language and conversation by the others. The root of this development is the desire for communication or to get into interaction with the environment (1). In the third, fourth and the fifth year of one’s life the vocabulary grows rapidly and the child starts to pick up the language rules. The communicational problem of the autistic people varies, depending on the intellectual and social status of the individual. The development of speech and language goes up to a certain degree, but not up to a level of normal ability. Some people’s speech is not developing at all, but others have a rich vocabulary and are able to talk about some topics of interest with a great curiosity. Many of them have a large memory for information which are just heard or seen; some have abilities to read, but not to understand what they read. Around 10% show outstanding abilities in specific areas as calendar calculation, talent for music or math (2). Most of them have a problem with the effective use of language and words, the meaning of a sentence, intonation and rhythm. This affects and disturbs the ability for interpretation and interaction with the environment. Some scientists connect these kinds of problems with the theory of mind or the reduced ability of thinking.
Keywords: autism